Whole-genome re-sequencing association study on body size traits at 10-weeks of age in Chinese indigenous geese - Sun, Guobo; Zhao, Hongchang; Mu, Xiaohui; Li, Xiaoming; Wang, Jun; Zhao, Mengli; Ji, Rongchao; Lv, Hailing; Li, Yang; Chen, Chao; Xie, Jia; Zhang, Wei; et al. (Frontiers in Veterinary Science, 2024)
To investigate the genetic factors underlying marketed body size traits in Chinese local geese, we conducted a comprehensive study involving nine body size traits in 251 samples at 10 weeks of age from five local breeds: Taihu goose (TH), Sichuan goose (SC), Guangfeng goose (GF), Xupu goose (XP), and Youjiang goose (YJ). Genotyping data were obtained through whole-genome re-sequencing, followed by a genome-wide association analysis utilizing the fixed and random model circulating probability unification (FarmCPU) approach. Our findings revealed 88 significant SNPs associated with body size traits, with 16 SNPs surpassing the genome-wide significance threshold (p = 3.98E-09) and 72 SNPs exceeding the suggestive significance threshold (p = 5E-07). Subsequent gene annotation identified these SNPs to be located within exonic regions of 86 candidate genes, including THADA, ATP5A1, ZNF462, PRDM8, and GH14523. Notably, functional enrichment analysis employing Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways highlighted 37 significantly enriched pathways, among which the “negative regulation of transforming growth factor beta receptor signaling pathway” (GO:0030512) emerged as relevant to goose skeletal development and the phenotypic expression of body size in geese. The identification of these novel SNPs and candidate genes associated with 10-week-old body size traits in geese presents valuable insights for future molecular breeding endeavors and the elucidation of underlying mechanisms governing body size trait formation in goose.